A systems approach to livestock research in sub-Saharan Africa - Neate, Paul J.H. (1988)
Livestock and crop-livestock systems are usually more complex than single cropping systems and are thus more difficult to "improve". The International Livestock Centre for Africa outlines experiences with systems research in projects in Nigeria and in the Ethiopian highlands.